Paroles d'Apollon : pratiques et traditions oraculaires dans l'Antiquité tardive, IIe-VIe siècle - Busine, Aude. (Religions in the Graeco-Roman World, 2005)
This book deals with the making and the reuses of the divine words which were ascribed to Apollo from the 2nd to the 6th centuries AD and which have now become available in both epigraphical and literary sources. The larger part has been issued by the sanctuaries of Claros and Didyma. This comprehensive and historical approach analyses the oracles of Apollo according to the various contexts ancient authors used to resort to the sacred words. The first part of the book examines, in the context of the Graeco-Roman city-states, the oracular texts in relation to the sanctuaries where they had originally been produced. The second part explores the different ways in which the Apollinian oracles were reappropriated by pagan and Christian authors for philosophical, polemical and apologetic purposes. This study of the sacred texts reveals in an original manner the cultural, political, and religious life of pagans and Christians in the Roman Empire.